The Effect of Genially-Based Interactive Media on Students’ Understanding of Mathematical Concepts - Siti Fatimah Sitorus; Isran Rasyid Karo-Karo S (Journal of General Education and Humanities, 2025)
This study aimed to determine the effect of using Genially interactive learning media on students’ understanding of mathematical concepts among grade X students at MAN 3 Medan. The research employed a quasi-experimental method with a pre-test and post-test design involving two groups: an experimental group that used Genially-based interactive learning and a control group that received traditional instruction. Two classes were randomly selected as samples. The data were collected using pre-test and post-test instruments that had been validated and tested for reliability. The results showed that students who were taught using Genially achieved higher post-test scores than those taught through conventional methods, with a mean difference of 13.4950 > . Statistical analysis revealed a significant difference between the two groups, suggesting that the use of Genially interactive media has a positive impact on students’ comprehension of mathematical concepts. The findings suggest that integrating Genially into classroom learning can enhance engagement, motivation, and conceptual understanding, making abstract mathematical material more concrete and accessible for students. Overall, the study highlights the potential of digital interactive media as a powerful tool for enhancing learning outcomes in mathematics education.